Intellectual disability : ethics, dehumanization, and a new moral community - Keith, Heather E.; Keith, Kenneth D. (Kenneth Dwight), 1946- (Chichester, West Sussex : J. Wiley, 2013)
"Intellectual Disability: Ethics, Dehumanization, and a New Moral Community presents an interdisciplinary exploration of the roots and evolution of the dehumanization of people with intellectual disabilities. This book: Examines the roots of disability ethics from a psychological, philosophical, and educational perspective ; Presents a coherent, sustained moral perspective in examining the historical dehumanization of people with diminished cognitive abilities ; Includes a series of narratives and case descriptions to illustrate arguments ; Reveals the importance of an interdisciplinary understanding of the social construction of intellectual disability."--Publisher's website.
Why study disability? -- Part I. The roots of dehumanization. Intellectual disability: history and evolution of definitions -- The social construction of Purgatory: ideas and institutions -- A failure of intelligence -- The consequences of reason: moral philosophy and intelligence -- Part II. Out of the darkness. Defining the person: The moral and social consequences of philosophies of selfhood -- Alternative views of moral engagement: relationality and rationality -- Culture and intellectual disability -- Part III. Disability ethics for a new age. Quality of life and perception of self -- Application and best practices: rights, education, and ethics -- Visions of the future.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: People with mental disabilities -- Cross-cultural studies; People with mental disabilities -- Social conditions; Mental illness -- Moral and ethical aspects; Mental illness -- Cross-cultural studies; Ethnopsychology -- Cross-cultural studies; Difference (Psychology) -- Cross-cultural studies; Group identity -- Cross-cultural studies; Social isolation -- Cross-cultural studies; SOCIAL SCIENCE -- People with Disabilities; Difference (Psychology); Ethnopsychology; Group identity; Mental illness; Mental illness -- Moral and ethical aspects; People with mental disabilities; People with mental disabilities -- Social conditions; Social isolation; Electronic books; Cross-cultural studies